Nonequilibrium action principles for quasi-ﬁeld - Burgess, M. (Condensed Matter Physics, 2000)
Quasiparticle descriptions of nonequilibrium physics hold the promise of tracking the relevant degrees of freedom in calculations of statistical systems, as well as providing an important formal perspective on quantum ﬁeld theories away from equilibrium. A formulation of nonequilibrium, quasiparticle ﬁeld theory is presented here. The Schwinger closed time path generating functional and generalized sources are used to develop schematic ﬁeld theories which can be adapted to real problems. The importance of the source method for effective nonequilibrium theories is argued and the physical interpretation of the formalism is discussed, including its possible applicability to biological dynamics.